NEW APPROACHES IN PREPARING FUTURE ENGLISH TEACHERS - Tajieva, A.U. (SCIENCE and SOCIETY, 2024)
The article is dedicated to explain the value of implementing new approaches into the educational process due to the requirements of time and society. Like the majority of countries, the Republic of Uzbekistan has further intensified the efforts to raise the activity of educational institutions to the level that can meet international requirements. In this regard, more attention has been paid to implementation of new approaches that give opportunity to gain modern knowledge based on world standards and can contribute to the development of the country. So, the presented article aims to describe one of the new approaches used in the country in the field of teacher preparation. PreSETT is a new curriculum for preparing future English teachers, the program which has successfully been implemented into the higher educational institutions. The results of the survey on identifying graduates and employers’ satisfaction with the program are discussed in the article, as well as the description of the program itself.
Keywords: PreSETT (Pre-Service English Teacher Training); new approach; curriculum; language module; methodological module; developing language skills; teaching skills